Still only one Earth : progress in the 40 years since the first UN Conference on the Environment - Harrison, Roy M., 1948-; Hester, R. E. (Ronald E.) ([Cambridge] : Royal Society of Chemistry, 2015)
Forty years since the first UN Conference on the Human Environment was held in Stockholm, how has the situation changed? We still have only one Earth but are we caring for and maintaining it? This book, written by leaders in the field, discusses the key environmental issues affecting the Earth today including atmospheric science, the marine environment, waste management and a specific chapter looking at changes in attitude to environmental issues. Aimed at policy makers, students, environmental scientists and thinkers, this title will be an important review bringing the reader right up to date with current opinions and attitudes.
Includes bibliographical references and index.
Keywords: Environmental sciences; Environmental policy